Women employee empowerment and job satisfaction in Nepalese commercial banks, Nepal - Saud, Dhan Bahadur (KVM Research Journal, 2025)
Women employee empowerment is a concept that has gained increasing significance in recent years. Commercial banks are typically structured around the principles of equality, democracy and solidarity and many of them have a long history of promoting women employee and inclusively within their membership and empowerment. The background of women employee empowerment in commercial banks can be traced back to the core values and principles that underpin the commercial banks movement.